The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/1523-1747.ep12338566
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Against Desmoplakin I and II Define a Subset of Patients with Erythema Multiforme Major

Abstract: In a previous report, we described autoantibodies against the desmosomal plaque proteins desmoplakin I and II (dp I and II) in patients with erythema multiforme (EM) major. In the present study we investigated ten EM major and eight EM minor patients for circulating autoantibodies and performed clinical and immunomorphological evaluations. Seven out of ten EM major patients revealed anti-dp I and II autoantibodies. Antigens were biochemically characterized by Western blotting and immunoprecipitation of epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…Recently, single case reports of overlapping antibody specificities in PNP and pemphigus vulgaris [17] and a case of bullous pemphigoid [27] have given evidence of further overlapping entities. Autoantibodies against desmoplakins I and II, initially thought to be pathognomonic for PNP, have lately also been found to occur under few other conditions: a subgroup of erythema multiforme major [28], PNP without detectable neoplasm (entire complex of antigens detectable) [29] and PNP with autoantibody deposition in bronchial epithelium after autologous bone marrow transplantation [30]. Mechanisms of true GVH disease [1, 2] may have been involved in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, single case reports of overlapping antibody specificities in PNP and pemphigus vulgaris [17] and a case of bullous pemphigoid [27] have given evidence of further overlapping entities. Autoantibodies against desmoplakins I and II, initially thought to be pathognomonic for PNP, have lately also been found to occur under few other conditions: a subgroup of erythema multiforme major [28], PNP without detectable neoplasm (entire complex of antigens detectable) [29] and PNP with autoantibody deposition in bronchial epithelium after autologous bone marrow transplantation [30]. Mechanisms of true GVH disease [1, 2] may have been involved in this case.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several reports demonstrate penetration of IgG autoantibody into living cells (19,20). Notably in keratinocytes, by using passive transfer and in vitro cell culture systems, a series of recent investigations have also demonstrated that IgG autoantibodies to desmoplakin I/II, entirely intracellular desmosomal antigens, can get into living cells and reach the target antigens (21)(22)(23). Moreover, anti-nuclear IgG antibodies from patients with systemic lupus erythematosus have been shown to penetrate into living epithelial cells via receptor-mediated endocytosis and subsequently localize to the corresponding intracellular target antigens (24).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the different outcome of our study compared with the initial work (Foedinger et al, 1995(Foedinger et al, , 1996 might be the tight window between diagnosis of the disease and serum sampling in our cohort. This may have reduced the detection of epiphenoma following the preceding tissue destruction due to an extended inflammatory response (Cozzani et al, 2011).…”
mentioning
confidence: 83%
“…Infiltrating TO THE EDITOR Erythema exsudativum multiforme majus (EEMM) is a rare condition affecting both skin and mucous membranes. It is assumed that humoral immune reponses may contribute to the pathogenesis of the disease, and the presence of autoantibodies was described in 7 of 10 EEMM patients (Foedinger et al, 1995(Foedinger et al, , 1996. These autoantibodies were associated with desmosomal staining by direct immunofluorescence microscopy of skin and by indirect immunofluorescence tests using monkey esophagus as a substrate, and they produced 210/ 250 kDa bands by immunoblotting of epidermal extracts, and immunoprecipitated proteins of apparently 210/250 kDa from lysates of human keratinocytes.…”
mentioning
confidence: 99%